Education on the Role of Electrolytes in Maintaining Heart Health for Students Al-Azhar Medan Private High School - Ritonga, Ahmad Hafizullah; Harefa, Karnirius; Herlina, Herlina; Sitorus, Rotua Sumihar; Harahap, Fitri Ramadani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2024)
Cardiac health is influenced by the balance of electrolytes in the body, such as sodium, potassium, calcium, and magnesium, which support cardiovascular functions, including heart rhythm and blood pressure regulation. Electrolyte imbalance increases the risk of heart disease, particularly among adolescents with unbalanced diets and low physical activity. Education about the role of electrolytes is essential for early prevention. This community service activity aimed to enhance the understanding of Al-Azhar Medan Private High School students as participants about the role of electrolytes in cardiac health and encourage them to adopt a healthy lifestyle. The methods included interactive counseling through presentations, discussions, and practical activities. The materials covered the types of electrolytes, their functions, signs of imbalance, and ways to maintain electrolyte balance through a healthy diet and adequate hydration. Visual aids and real-life case examples were utilized to clarify the participants' understanding. The evaluation results showed a significant improvement in the participants' knowledge of electrolyte functions and the importance of electrolyte balance for cardiac health. Most participants expressed an intention to pay more attention to their diet and electrolyte intake, and the program was effective in increasing knowledge and awareness of the importance of electrolytes for heart health. Proper education is expected to encourage adolescents to adopt a healthy lifestyle early, reducing the risk of heart disease in the future.